EFEKTIVITAS ORANG TUA SEBAGAI TENAGA PENDIDIK DALAM UPAYA MEMPERTAHANKAN KELUARGA DI MASA PANDEMI COVID-19 - Azhari, Hulaimi (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2020)
This study aims to know in-depth the effectiveness of children's learning through the direct upbringing of parents in lieu of teachers in schools during the covid-19 pandemic era. Seeing the phenomenon that occurred when the covid-19 outbreak arrived in Indonesia where the pattern of people's lives has changed. It is characterized by the number of people who are lost to their jobs, shrinking the value of labor income, weakening the State economy, and face-to-face lessons that are matched by the pandemic so as to impose the active role of parents in lieu of teacher duties. This means that in addition to being a livelihood seeker for the sustainability of family life, a parent also acts as a teacher. This is the background of this research. This study took place in kelebuh village, Praya Tengah sub-district, Central Lombok regency. Next, this research type of field research (field research) with the method of analysis is inductive. While the approach used is an empirical approach based on the theory of effectiveness. The findings showed the success and effectiveness of parental function in the actualization of work from home. The success of the three parents in Kelebuh village gives an indication that efforts to maintain the existence of the family in the covid-19 period are realized and categorized as successful.